2019
DOI: 10.1111/jonm.12785
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and work‐related disease underestimated and linked to temporary disability through Primary Health Care Services

Abstract: Aim:To estimate the occupational disease linked to temporary incapacity (not workrelated illness). Background:The under-reporting of occupational disease is a recognized problem in Europe. Methods:Cross-sectional study conducted in Spanish adult population using periods of temporary incapacity recorded in primary care during 2015. Rates of occupational disease were estimated using the García & Gadea study. Results:A total of 130,771 episodes of temporary incapacity were studied from 91,448 people, and 56,092 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These findings were noted in a high number of nurses. 5 , 6 Therefore, the incidence of occupational diseases may be more serious than that previously reported. Multiple occupational diseases can lead to the decline of physical functions and decreased working efficiency, which can affect their job satisfaction, the career planning and development of the nurses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings were noted in a high number of nurses. 5 , 6 Therefore, the incidence of occupational diseases may be more serious than that previously reported. Multiple occupational diseases can lead to the decline of physical functions and decreased working efficiency, which can affect their job satisfaction, the career planning and development of the nurses.…”
Section: Discussionmentioning
confidence: 96%
“…These factors are responsible for causing the occurrence of occupational diseases. 6 The World Health Organization (WHO) estimated the work-related burden of disease and injury with the aid of experts. Evidence from data has suggested that occupational exposure to risk factors may cause osteoarthritis and other musculoskeletal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational disease occurrence is commonly underreported—up to 90% of occupational diseases are undeclared for some pathologies. 15 The prevalence of undeclared AK and the short-term consequences for sick leave are unknown. Owing to the risk of contaminating the patient and the operating room, infected doctors stop surgery while they are still contagious.…”
mentioning
confidence: 99%